Tổng hợp và cấu trúc dãy hợp chất azometin từ axit 5-amino-2-metoxi-4-(3-metylfuroxan-4-yl)phenoxyaxetic - Lan, Hoàng Thị (Vietnam Journal of Chemistry, 2016)
catalysts, medicine, crystal engineering, anti-corrosion agent. Many compounds contained furoxan ring, a nitric oxide (NO) releasing moiety, display a variety of biological activities, for example anti-inflammatory activity, the vasodilator activity and the inhibition of platelet aggregation. In recent years, several classes of hybrid compounds, obtained combining appropriate pharmacophoric groups with NO-releasing functions, have been described, such as NO-aspirin, NO-steroids and NO-guanidines, some of these compounds are now under clinical investigations. In this paper, 2-methoxy-4-(3-methylfuroxan-4-yl)-5-nitrophenoxyacetic acid (synthesized from eugenol) was reduced with Na2S2O4 in NaOH to give 5-amino-2-methoxy-4-(3-methylfuroxan-4-yl)phenoxyacetic acid. The latter was used as key compound for synthesis of a series of 11 new azomethines containing furoxan ring by condensation with various aromatic aldehydes. The obtained azomethines (the yield of 45-69%) are crystalline solids with melting points of 126-235 oC. The structure of the azomethines was determined by analyzing their IR, 1H NMR and MS for some compounds. All resonance signals in the 1H NMR spectra of examined compounds were accurately assigned based on analyzing the spin-spin splitting patterns, for some compounds 2D NMR was also used. Keywords. Azomethine, Schiff base, furoxan, eugenol.